Political and juridical analysis of the territorial dispute between Bolivia and Chile and prospects of its settlement - Solovyev, Nikita (Iberoamerikanskie tetradi, 2016)
The article dwells upon the political and juridical analysis of the territorial dispute between Bolivia and Chile. There was conducted the analysis of Bolivian lawsuit against Chile in the International Court of Justice, were pointed out the peculiarities of the case, were subjected to analysis the positions of the two countries towards the dispute The author makes conclusions about the prospects of resolution of the dispute and its contribution to the international law